1996
DOI: 10.1021/ja961597e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Search for CH53+ and CH64+ and Their Isoelectronic Boron Analogues BH52+ and BH63+1

Abstract: The structures and stabilities of CH5 3+ and CH6 4+ and their isoelectronic boron analogues BH5 2+ and BH6 3+, respectively, were calculated at the MP2/6-31G** and QCISD (T)/6-311G** levels. The planar D 5 h symmetric structure 3 is a minimum for the CH5 3+ trication. The five hydrogens in structure 3 are bonded to the carbon atom by sharing the six valence electrons. Calculations showed that the CH6 4+ tetracation does not correspond to a minimum at the levels studied. The planar C 2 v symmetric structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…We recently reported (21) that the planar D 5h symmetric structure 5 is an energy minimum for the CH 5 3ϩ trication. On the other hand, our calculations showed that the energy-minimum structure of isoelectronic boron analog, the BH 5 2ϩ dication has the planar C 2v symmetric structure 6, with two 2eO3c bonds (21).…”
mentioning
confidence: 75%
“…We recently reported (21) that the planar D 5h symmetric structure 5 is an energy minimum for the CH 5 3ϩ trication. On the other hand, our calculations showed that the energy-minimum structure of isoelectronic boron analog, the BH 5 2ϩ dication has the planar C 2v symmetric structure 6, with two 2eO3c bonds (21).…”
mentioning
confidence: 75%
“…There is a consistent pattern to be found in examining the geometries of the BH 2 Table 3) are also noted. This is not unlike the situation found in geometry optimized [13] and ‫ם‬ CH 5 [14], entities containing two hydrogens that CH BH 3 3 cule. This is in contrast with the protonated benzene, C 6 [12] (which is thought to be involved as an in-‫ם‬ H 7 termediate in H/H proton exchange in AlCl 3 /HCl promoted reactions); the CH 2 group has rather more standard C-H distances (Ϸ1.1 Å ) and an H • • • H distance (Ϸ1.7 Å ) suggesting very little H-H bonding.…”
Section: Mechanism Of D/h Exchangementioning
confidence: 70%
“…Thus, the calculated structure for the protonated carborane species could well imply that the boron of the BH 2 group is sharing a pair of H-H r electrons, just as it could be implied [14] for the special bonding situation in "stable species" of and .…”
Section: Figurementioning
confidence: 86%